Facile Synthesis of Manganese Cobalt Oxide/Nickel Cobalt Oxide Composites for High-Performance Supercapacitors - Huo, Wang Chen; Liu, Xiao Li; Yuan, Yun Song; Li, Nan; Lan, Tian; Liu, Xiao Ying; Zhang, Yu Xin (Frontiers in Chemistry, 2019)
Transition metal oxides (TMOs) with spinel structures have a promising potential as the electrode materials for supercapacitors application owning to its outstanding theoretical capacity, good redox activity and eco-friendly feature. In this work, MnCo2O4.5@NiCo2O4 nanowire composites for supercapacitors has been successfully fabricated by using a mild hydrothermal approach without any surfactant. The morphology and physicochemical properties of the prepared products can be well controlled by adjusting experimental parameters of preparation. The double spinel composite exhibits a high specific capacitance of 325 F g-1 (146 C g-1) and 70.5% capacitance retention after 3000 cycling tests at 1 A g-1.